Ichnotaxonomic revision of Ameghinichnus, a mammalian ichnogenus from the Middle Jurassic La Matilde Formation, Santa Cruz province, Argentina - de Valais, Silvina (Zootaxa, 2009)
The ichnological assemblage from the Estancia Laguna Manantiales, from the Middle Jurassic La Matilde Formation, Santa Cruz province, Argentina, is exceptional both in diversity and abundance. It is composed of mammal, dinosaur, invertebrate, and root traces. The most significant and abundant specimens are those assigned to the ichnogenus Ameghinichnus Casamiquela, 1961. This ichnogenus is revised and an emendation of its diagnosis is suggested. The inclusion of all the known specimens to the type ichnospecies, Ameghinichnus patagonicus Casamiquela, 1961, is challenged and some specimens are placed in a new ichnospecies, Ameghinichnus manantialensis isp. nov. Similar tracks from other ichnological localities worldwide were previously referred to Ameghinichnus, but only Eopentapodiscus (Ellenberger, 1970), from South Africa is considered as a junior synonym of Ameghinichnus. The ichnotaxobases used to classify tracks with mammalian affinities at ichnogeneric and ichnospecific levels are evaluated and re-assessed ichnotaxonomic criteria are proposed. Different criteria used to distinguish mammalian imprints from non-mammalian tracks are commented.